2019
DOI: 10.3390/magnetochemistry5030045
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Application of Iron Oxide Nanoclusters

Abstract: Magnetic iron oxide nanoclusters, which refers to a group of individual nanoparticles, have recently attracted much attention because of their distinctive behaviors compared to individual nanoparticles. In this review, we discuss preparation methods for creating iron oxide nanoclusters, focusing on synthetic procedures, formation mechanisms, and the quality of the products. Then, we discuss the emerging applications for iron oxide nanoclusters in various fields, covering traditional and novel applications in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Thus, the obtained SPION-PEG clusters are suitable for many in vivo applications, either as enhanced contrast agents or as an alternative treatment of various tumors, through hyperthermia. Studies have shown that clustering of small SPIONs increases contrast due to magnetic field inhomogeneities and offers better MRI resolution than current FDA-approved Ferucarbotran, used at the same dose [ 28 , 95 ]. For future studies, the aspect of cluster size may be further addressed to avoid aggregation, as from the standpoint of histology, ultrastructure, and clearance, we consider the SPION-PEG clusters biocompatible platforms that are appropriate for application after specific adjustments and upgrades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the obtained SPION-PEG clusters are suitable for many in vivo applications, either as enhanced contrast agents or as an alternative treatment of various tumors, through hyperthermia. Studies have shown that clustering of small SPIONs increases contrast due to magnetic field inhomogeneities and offers better MRI resolution than current FDA-approved Ferucarbotran, used at the same dose [ 28 , 95 ]. For future studies, the aspect of cluster size may be further addressed to avoid aggregation, as from the standpoint of histology, ultrastructure, and clearance, we consider the SPION-PEG clusters biocompatible platforms that are appropriate for application after specific adjustments and upgrades.…”
Section: Discussionmentioning
confidence: 99%
“…Metal nanoclusters are a new type of platform that have different characteristics than singular nanoparticles. (Ultra)small nanoclusters (<20 nm) have been proven to have increased efficiency for catalytic, photoluminescence, coulorimetric, chemodynamic, and sensor activity in comparison with large-size nanoparticles [ 24 , 25 , 26 , 27 , 28 ]. However, due to their size, they can interfere with normal metabolic activities in the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis and Characterization of Iron Oxide Nanoclusters. The iron oxide nanoclusters (∼200 nm) were synthesized using our well-established protocols 43,44 by heating the reactants (iron chloride, sodium acetate, and PAA) in ethylene glycol in a sealed Teflon-lined stainless steel hydrothermal reactor at 200 °C. In brief, FeCl 3 (0.8 mmol, 0.129 g) was dissolved in 30 mL of ethylene glycol followed by the addition of PAA water solution (8 mmol, 0.52 g) and sodium acetate (35 mmol, 2.87 g).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Alternatively, a clustering process can be produced through a direct aggregation of NPs during synthesis. (37,38) The polyol method has extensively been used in the last decade for this purpose. (39,40) Its versatility enables the formation of different types of aggregates with controlled morphologies ranging from nanoclusters to nanoflowers and hollow spheres.…”
Section: Introductionmentioning
confidence: 99%